Comprehensive parameter identification of feed servo systems with friction based on responses of the worktable. (December 2015) - Liu, Lilan; Wu, Ziying
Abstract: A comprehensive identification method for structure and friction parameters of feed servo systems is put forward. A motor direct-connected feed system with Stribeck friction law is investigated. The relation between the critical stick-slip velocity of the worktable and the structure parameters as well as the difference between the static and Coulomb friction coefficient is derived first. Then, according to the data of critical stick-slip velocities at different feed positions, the structural parameters (such as diameter, lead and bearing length of the ball screw) are estimated using the nonlinear least square method. Furthermore, based on the stick-slip displacement response of the worktable, the Stribeck friction parameters are obtained using the direct graphical registration method. The feasibility and validity of the presented identification method is verified by numerical simulation. All the work can provide a theoretical reference for the comprehensive parameters identification of feed systems.